Product Standards, Harmonization, And Trade : Evidence From The Extensive Margin - Shepherd, Benjamin 1993- (The World Bank, 2007)
The author uses a new database of EU product standards in the textiles, clothing, and footwear sectors to present the first empirical evidence that international standards harmonization is associated with increased partner country export variety. A 10 percentage point increase in the proportion of internationally harmonized standards is associated with a 0.2 percent increase in partner country export variety, whereas a 10 percent increase in the total number of standards is associated with a nearly 6 percent decrease in product variety. Although small, the harmonization elasticity is statistically significant, and proves highly robust to sample changes and instrumental variables estimation using instruments motivated by political economy considerations. Moreover, it is found to be around 50 percent higher for low income countries, which suggests that they may be particularly constrained in adapting products to meet multiple standards. Numerical simulations show that these findings are consistent with a heterogeneous firms model of trade in which harmonization is beneficial at the extensive margin provided that any increases in compliance costs are not too large